Assessing of Photoluminescence and Thermoluminescence Properties of Dy3+ Doped White Light Emitter TTB-Lead Metatantalate Phosphor - (:unkn) unknown (SPRINGER, 2020)
Trivalent Dy doped TTB (tetragonal tungsten bronze) lead tantalate (PbTa2O6) phosphors were synthesized by the solid-state reaction route. Structural and spectroscopic properties have been carried out by x-ray diffraction (XRD), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), photoluminescence (PL) and thermoluminescence (TL) analyses. XRD patterns of samples revealed the presence of TTB symmetry which continued up to 10 mol.%. SEM analysis showed the transformation of grain morphology from the shapeless-rounded to elongate. Strong PL emissions of PbTa2O6:Dy3+ phosphor were monitored at 480.5 nm and 578.5 nm. PL emission increased up to 7 mol.% and then decreased because of the concentration quenching. Decay times decreased with the increase of concentration and the end of the process (10 mol.%) fell to 355 mu m. The energy transfer efficiency (eta(ET)) energy transfer rate (W) and quantum efficiency (eta(QE)) of the whole process were found as 56.25%, 1.581 ms(-1), and 20.27%, respectively. The CIE (Commission Internationale de l'eclairage) coordinates of all phosphors have located close to the standard white light center, also the CIE coordinates (x, y) and CCT (correlated color temperature) value for 7 mol.% phosphor were found as (0.310, 0.295) and 6238 K, respectively. TL emissions of PbTa2O6:Dy3+ phosphor were monitored by four glow peaks in the range between 50 degrees C and 400 degrees C after x-ray irradiation. TL kinetic parameters were determined by the deconvolution of the 5 mol.% sample which has the highest glow curve intensity.
Keywords: Leadtantalate; XRD; photoluminescence; W-LEDs; thermoluminescence; GOODNESS-OF-FIT; ENERGY-TRANSFER; LUMINESCENCE PROPERTIES; EU3+ IONS; COLOR; RAY; NASR2NB5O15; TEMPERATURE; NIOBATE